Print by Marvin Oliver, "New Generation," 1997 (1997)
This serigraph by Native American sculptor and printmaker Marvin Oliver (1946-2019) depicts a new generation of salmon hatching from eggs. Born to Quinault and Isleta-Pueblo parents, and raised in Washington and San Francisco, Marvin Oliver was an Associate Professor of American Indian Studies and Art History at the University of Washington and Curator of Contemporary Native American Art at the Burke Museum. A popular contemporary sculptor and printmaker, Oliver has been recognized nationally and internationally for his monumental works in cedar, bronze, cast glass, and enameled steel. His work often demonstrates a fusion of ancient forms with a modern aesthetic, and is widely exhibited in the US and abroad in addition to being on display at his galleries in Seattle and in Ketchikan, Alaska. 1 Print, Embossed; Materials: Paper --Ink --Red --Black --Wood --Plexi; Dimensions: Art: 19 in.H x 28 in.W Frame: 29 in.H x 31.25 in.W x 2 in.D